Empirical evaluation of asset pricing models: Arbitrage and pricing errors over contingent claims - Zhenyu Wang; Xiaoyan Zhang (Federal Reserve Bank of New York, 2006)
Hansen and Jagannathan (1997) have developed two measures of pricing errors for asset pricing models: the maximum pricing error in all static portfolios of the test assets and the maximum pricing error in all contingent claims of the assets. In this paper, we develop simulation-based Bayesian inference for these measures. While the literature reports that the time-varying extensions substantially reduce pricing errors of classic models on the standard test assets, our analysis shows that the reduction is much smaller based on the second measure. Those time-varying models have pricing errors on the contingent claims of the test assets because their stochastic discount factors are often negative and admit arbitrage opportunities.
Keywords: G1; G12; 330; Bayesian inference; asset pricing; pricing errors; model comparison; contingent claims; Capital Asset Pricing Model; Arbitragegeschäft; Theorie